2018
DOI: 10.1245/s10434-018-6763-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Extensive Lymph Node Metastases for Resected Pancreatic Cancer

Abstract: The prognostic impact of extensive lymph node spread after resection for PDA plateaus above a specific threshold (LNC ≥ 4 or LNR ≥ 0.4), supporting the new 8th edition AJCC criteria for N2 disease. Clinically, lymph node spread above this threshold seems to correlate with occult systemic disease (elevated postoperative CA 19-9 and systemic pattern of failure).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
0
23
0
3
Order By: Relevance
“…Lymph node metastasis is a poor prognostic factor in patients with PDAC [5][6][7][8]12]. To better understand the relationship between lymph node size and metastases, we comprehensively evaluated all harvested lymph nodes by measuring the size along the long and short axes and compared the lymph node size and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymph node metastasis is a poor prognostic factor in patients with PDAC [5][6][7][8]12]. To better understand the relationship between lymph node size and metastases, we comprehensively evaluated all harvested lymph nodes by measuring the size along the long and short axes and compared the lymph node size and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node metastasis is a poor prognostic factor in patients with PDAC [5][6][7][8]. Nodal status and quantity are important, and nodal (N) staging is classified based on the number of metastatic lymph nodes, as N0 (0), N1 (1-3), and N2 (≥ 4), in the 8th edition of the American Joint Committee on Cancer [9].…”
mentioning
confidence: 99%
“…A high postoperative CA19‐9 level is a well‐established biomarker predicting the prognosis of patients with resected PDAC 4,10‐14 . A high postoperative CA19‐9 level (>37 U/mL) is a risk factor affecting early postoperative recurrence and poor survival 15‐17 .…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…5,12,13 Asano et al showed that the median overall survival was 56 months in the N0 group, 34 months in the N1 group, and 20 months in the N2 group for patients with pancreatic head ductal adenocarcinoma who underwent pancreaticoduodenectomy. 6 Lowder et al 9 found that N2 staging was correlated with postoperative CA19-9 levels (P ¼ .044) and systemic recurrence (P < .001), indicating that extensive lymph node involvement may be associated with occult systemic disease. In this study, patients with N0 (P ¼ .006) or N1 (P < .001) disease were susceptible, while patients with N2 disease (P ¼ .867) were resistant to gemcitabine-based adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%